EVO Teacher's Guide : Ten Questions Everyone Should Ask About Evolution (Book). - Bybee, Rodger W. (National Science Teachers Association (NSTA), 2012)
Draw on the wit and wisdom of brilliant scientists to inspire your students as you teach them about a challenging area of biology. This teacher?s guide, which accompanies the EVO DVD, is structured around 10 fundamental questions about biological evolution. The teachers guide explores the DVD?s commentary from some of the world?s most well-known biologists, who gathered on the Galápagos Islands during a World Summit on Evolution and were interviewed about everything from what evolution is to how it happens to why anyone should care.